Modification changes the anatomical structure of the vegetative organs of new rice varieties (Eurasian Journal of Ecology, 2016)
The formation of the anatomical structure of stems, leaves, roots, new rice varieties has a significant impact agroenvironmental factors (nutrition area, dose, timing and metods of application of fertilizers).
Keywords: rice; stem; leaves; roots; their anatomical structure; agro-ecological factors (nutrition area; dose; timing and methods of fertilizers).